2011
DOI: 10.1007/s10551-011-1040-5
|View full text |Cite
|
Sign up to set email alerts
|

Love of Money and Unethical Behavior Intention: Does an Authentic Supervisor’s Personal Integrity and Character (ASPIRE) Make a Difference?

Abstract: We investigate the extent to which perceptions of the authenticity of supervisor's personal integrity and character (ASPIRE) moderate the relationship between people's love of money (LOM) and propensity to engage in unethical behavior (PUB) among 266 part-time employees who were also business students in a five-wave panel study. We found that a high level of ASPIRE perceptions was related to high love-of-money orientation, high selfesteem, but low unethical behavior intention (PUB). Unethical behavior intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(67 citation statements)
references
References 139 publications
(209 reference statements)
4
62
1
Order By: Relevance
“…It is important to note that the dissonance lies in the leader, rather than in the followers. Similarly we found the Machiavellian effect had the same inversion pattern on the link between authentic leadership and moral action, corroborating prior study which reported that high Machiavellianism would lead to both unethical intentions and acts (Tang and Liu 2012). That is to say, just because a leader is perceived to be authentic, it does not necessarily mean that they will engage in moral action-at least not consistently.…”
Section: Discussionsupporting
confidence: 90%
“…It is important to note that the dissonance lies in the leader, rather than in the followers. Similarly we found the Machiavellian effect had the same inversion pattern on the link between authentic leadership and moral action, corroborating prior study which reported that high Machiavellianism would lead to both unethical intentions and acts (Tang and Liu 2012). That is to say, just because a leader is perceived to be authentic, it does not necessarily mean that they will engage in moral action-at least not consistently.…”
Section: Discussionsupporting
confidence: 90%
“…On the negative side, the love of money motive predicts subsequent unethical intentions in multiple panel studies and cheating behaviors in laboratory experiments (Chen et al 2014;Tang and Chen 2008;Tang and Liu 2012). Using a formative model of MI, the combination of positive love of money motive and poor (negative) stewardship behavior leads to unethical intentions .…”
Section: Hypothesis 1 Students Improve Their Ethical Decision Making mentioning
confidence: 99%
“…''Money wise'' college students Fig. 5 Results of our theoretical model of MImoney attitudes and two outcomes (intrinsic religiosity vs. the Ten Commandments) remain faithful to what they have learned from their parents during childhood (Chaplin and John 2010), embrace the sacred values (honesty, integrity, and character) (Tang and Liu 2012), are equipped with wisdom for virtuous behavior, and become competent for academic course work. With different measures of money attitudes and consequences and different samples across cultures, the love of money motive provides consistent theoretical implications.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…They must implement organizational corruption control elements-bureaucratic control, punishment, incentive alignments, legal/regulatory sanctioning, social sanctioning, vigilance controls, self-control, and concertive controls (Lange 2008). It is also practical to rotate these top level executives to different positions/ divisions in order to avoid having long-term control of power and authority, improve the work environment, valorize corporate ethical values, inspire personal integrity (Simons 2002;Simons et al 2007;Tang and Liu 2011), and manage all stakeholders (stockholders, managers, employees, suppliers, and customers) fairly to reduce corruption and increase profits. Future research may test this proposition.…”
Section: Practical Contributionsmentioning
confidence: 99%